Dietary vitamin D intake among university students and their habits concerning daily sunlight exposure : a cross-sectional study = Unos vitamina D prehranom među studentima i njihove navike s obzirom na izlaganje sunčevoj svjetlosti : presječno istraživanje - Kenđel Jovanović, Gordana (Array, 2021)
Aim: To evaluate students" dietary vitamin D intake according to characteristics and habits concerning daily sunlight exposure. Methods: The study included 403 students of the University of Rijeka, Croatia that fulfilled questionnaire about their characteristics, habits, physical activity, supplement use, diet, and their daily sunlight exposure. For assessing diet quality, the Dietary inflammatory index (DII®) was used.